Tata McGraw Hill Education Private Limited - Dixit, Mukund R.; Anil Kumar, H. ([London] : SAGE, 2016)
This case presents details of the origin, strategy, and performance of Tata McGraw Hill Education Private Limited. It describes the initiatives of Mr Shukla, Managing Director and Vice President, in maintaining the leadership of the company in a changing environment.
Originally Published in: Dixit, M., & Kumar, A. (2015). Tata McGraw Hill Education Private Limited. BP0382. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 3, 2016).
Keywords: elektronické knihy; electronic books; Tata McGraw Hill Education (Firm); Competition -- Case studies; Strategic planning -- Case studies; Organizational change -- Case studies; Leadership -- Case studies